Uncharted territory: retinal vasculitis and cryoglobulinemia in Behçet’s disease – a case report - Zou, Yadan; Yang, Kun; Zhang, Xiaoying; Li, Sheng-Guang (Frontiers in Immunology, 2025)
Behçet’s disease (BD) is a systemic inflammatory disorder characterized by recurrent oral and genital ulcers, skin lesions, and ocular involvement, often presenting with retinal vasculitis as a severe complication. Although mixed cryoglobulinemia, typically associated with hepatitis C virus (HCV) infection, is well-documented in other autoimmune diseases, its coexistence with BD is exceedingly rare. This report details the case of a 56-year-old male presenting with BD complicated by HCV-related mixed cryoglobulinemia, manifesting as retinal vasculitis, purpuric skin lesions, and systemic vasculitis. Despite initial corticosteroid treatment, the patient required escalated therapy, including immunosuppressants and antiviral agents, to achieve disease stability. This case underscores the need for a multidisciplinary approach in managing BD with secondary cryoglobulinemia and highlights the complex interplay between autoimmune and viral-induced vasculitis. Our findings contribute to the literature by documenting a rare presentation of BD and providing insights into comprehensive treatment strategies for similar cases.